2020
DOI: 10.1002/bab.1862
|View full text |Cite
|
Sign up to set email alerts
|

Biochar reduces nutrient loss and improves microbial biomass of composted cattle manure and maize straw

Abstract: In this study, nutrient loss, the direct and indirect relationship between period, compost types, temperature, total nitrogen (TN), nitrate nitrogen (NO 3 −-N), ammonium nitrogen (NH 4 +-N), microbial biomass carbon (MBC), and microbial biomass nitrogen (MBN) were investigated during composting of cattle manure-maize straw mixture. This study findings revealed that biochar addition lowered NH 4 +-N but did not increase NO 3 −-N concentrations unlike no biochar piles during composting. The first-order kinetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 67 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…Lower values of N were also seen in the case of biochar produced at 650 • C. Although some authors claimed that biochar-amended piles showed significantly higher N content in comparison to control treatments, in our study we did not clearly confirm this trend. Nevertheless, processes that have an impact on nitrogen dynamics are complex, and reports of enriching N content in the biochar-composted material involve longer incubation times, of up to 40 days [81,82]. On the other hand, presented observations support the theories that despite the role of biochar in the mitigation of carbon and nitrogen losses from composting processes, the final C/N ratio in the material is not significantly affected by the addition of biochar.…”
Section: Effect Of Biochars On Nutrients and Heavy Metal Content Duri...supporting
confidence: 68%
“…Lower values of N were also seen in the case of biochar produced at 650 • C. Although some authors claimed that biochar-amended piles showed significantly higher N content in comparison to control treatments, in our study we did not clearly confirm this trend. Nevertheless, processes that have an impact on nitrogen dynamics are complex, and reports of enriching N content in the biochar-composted material involve longer incubation times, of up to 40 days [81,82]. On the other hand, presented observations support the theories that despite the role of biochar in the mitigation of carbon and nitrogen losses from composting processes, the final C/N ratio in the material is not significantly affected by the addition of biochar.…”
Section: Effect Of Biochars On Nutrients and Heavy Metal Content Duri...supporting
confidence: 68%
“…Therefore, adding biochar to early composting mixes has been recommended as an effective management approach for reducing nitrogen loss. In the original composting material, a diverse set of biochar ratios from 3 to 50% has been employed, and an addition of about 10% is typically suggested for maximum composting concert (Awasthi et al, 2017;Bello et al, 2020;Liu et al, 2017b;Wang et al, 2017b). In certain studies, biochar has been employed as a filler in chicken manure composting and has resulted in a significant increase in the rate of degradation (up to 70%), as well as a reduction in odour, gas emissions, and nitrogen loss (Dias et al, 2010;Liu et al, 2017b).…”
Section: Environmental Remediation and Compostingmentioning
confidence: 99%
“…MBC has been used to reduce pollution in wastewater, soil and gas. MBC, as a good soil improvement, may not only enhance the physiochemical characteristics of the soil but also immobilize or eliminate heavy metals, adsorb and breakdown organic pollutants from the soil (Mandal et al, 2020a(Mandal et al, , 2020bQin et al, 2020;Wu et al, 2020). MBC has been successfully utilized to remove hazardous chemicals from flue gas for gas pollution control (Shan et al, 2019).…”
Section: Magnetic Biochar Catalyst (Mbc)mentioning
confidence: 99%
“…Bello et al. [11] tested Biochar addition, within cattle manure composting process, as a positive modulator in the nitrogen transformation process. The results indicate that Biochar addition accelerated organic matter degradation and improved nitrogen mineralization.…”
Section: The Role Of Positive or Negative Modulators On Biofuel Produmentioning
confidence: 99%